Perancangan Digital Prototype of Foot-Operated Handsanitizer Stand - Hadi Saputra (Jurnal Teknologi, 2022)
Research shown that the use of 17 drum hand sanitizers in the ICU surgical department was 100% contaminated with bacteria. During this pandemic, the transmission of the spread of the coronavirus must be reduced. You do this by using hand sanitizer liquid without touching the bottle. The economic conditions of the people who were affected during the pandemic have inspired to innovate existing hand sanitizer stand products. It is hoped that this research can produce a foot-operated hand sanitizer stand that is cheap and easy to manufacture. Innovation is done by making digital prototypes using Computer-Aided Design (CAD) and Computer-Aided Engineering (CAE). This research has produced a digital foot-operated hand sanitizer stand that is simple, easy to manufacture, and with materials that are easily available in the market.